Analysis on the Low Speed Performance of an Inward-Turning Multiduct Inlet for Turbine-Based Combined Cycle Engines - Chengxiang Zhu; Haifeng Zhang; Zhancang Hu; Yancheng You (International Journal of Aerospace Engineering)
The multiduct inlet for turbine-based combined cycle engines receives a lot of attention on its aerodynamic performance. Aside of the most studied mode of transition processes, another significant severe issue regarding the aerodynamic performance of the turbine duct (T-duct) at ground states has rarely been investigated which indeed directly determines the operability and reality of similar engine systems; this issue will be addressed in the present work. Our numerical and experimental studies of an inward-turning tetraduct inlet indicate that the performance of the T-duct is seldom affected by the angle of attack, which however is of crucial importance for takeoff/landing of flight vehicles. The two T-ducts exhibit weak asymmetrical aerodynamic performance during experiment due to nonsynchronization as well as mechanical oscillation of the two turbine engines. With increasing inflow speed, the surface pressure and the total pressure recovery increase accordingly. At Ma∞=0.24, the total pressure recovery achieves 0.96 at the exit of the turbine duct which is acceptable for the engine to generate sufficient thrust for horizontal takeoff. A further quantitative comparison between simulation and experiment reveals a maximum deviation of only 3% in terms of both surface pressure and total pressure recovery.